Strategies for the production of difficult-to-express full-length eukaryotic proteins using microbial cell factories : production of human alpha-galactosidase A - Unzueta Elorza, Ugutz; Vázquez Lima, Felícitas; Accardi, Giulia; Mendoza, Rosa; Toledo-Rubio, Verónica; Giuliani, Maria; Sannino, Filomena; Parrilli, Ermenegilda; Abasolo, Ibane; Schwartz, Simon; Villaverde Corrales, Antonio; Corchero Nieto, José Luis; et al. (Applied Microbiology and Biotechnology, 2015)
This work was supported by ERANET-IB08-007 project from the European Union and its linked national project EUI2008- 03610 to AV. We also appreciate the support from EME2007-08 to NFM from Universitat Autonoma de Barcelona, from Antartide 2010 to MLT and EP, from MIUR Azioni Integrate Italia-Spagna 2010 Prot. IT10LECLM9 to MLT, from MINECO (IT2009-0021) to AV and LT, from AGAUR (2009SGR-108) to AV. AV is also supported by The Biomedical Research Networking Center in Bioengineering, Biomaterials and Nanomedicine (CIBER-BBN, Spain), an initiative funded by the VI National R&D&i Plan 2008-2011, Iniciativa Ingenio 2010, Consolider Program, CIBER Actions and financed by the Instituto de Salud Carlos III with assistance from the European Regional Development Fund. PS has received predoctoral fellowship from ISCIII, and AV has been distinguished with an ICREA ACADEMIA award (Catalonia, Spain). Obtaining high levels of pure proteins remains the main bottleneck of many scientific and biotechnological studies. Among all the available recombinant expression systems, Escherichia coli facilitates gene expression by its relative simplicity, inexpensive and fast cultivation, well-known genetics and the large number of tools available for its biotechnological application. However, recombinant expression in E. coli is not always a straightforward procedure and major obstacles are encountered when producing many eukaryotic proteins and especially membrane proteins, linked to missing posttranslational modifications, proteolysis and aggregation. In this context, many conventional and unconventional eukaryotic hosts are under exploration and development, but in some cases linked to complex culture media or processes. In this context, alternative bacterial systems able to overcome some of the limitations posed by E. coli keeping the simplicity of prokaryotic manipulation are currently emerging as convenient hosts for protein production. We have comparatively produced a "difficult-to-express" human protein, the lysosomal ...